Etika Berpakaian bagi Kaum Perempuan Dalam Ibadah Menurut I Timotius 2:9-10 dan Aplikasinya Masa Kini - Asni Darmayanti Duha (Sekolah Tinggi Teologi Berita Hidup, 2020)
Abstract: Ethics are important things in human life, and clothing is a human need that cannot be ignored. Dress ethics shows the character of life and a good way of life in the midst of an increasingly secular and uncontralized world. Of course Christians cannot be influenced by the development of the times. Christians must live according to the truth of God's Word. Good and polite dress ethics are the wealth and glory of women. In worship there are many ways to dress that are not polite. A woman who is good and takes care of her honor keeps her dress code. In this case, the writer uses the method of literature and ecegesis based on the text which becomes the author's reference to reveal the truth about dressing.Abstrak: Etika merupakan hal penting di dalam kehidupan manusia, dan pakaian adalah kebutuhan manusia yang tidak bisa diabaikan. Etika berpakaian menunjukkan karakter hidup dan cara hidup yang baik di tengah dunia yang semakin sekular dan tidak terkontral ini. Tentu orang Kristen tidak dapat terpengaruh dengan perkembangan zaman yang ada. Orang Kristen harus hidup sesuai dengan kebenaran Firman Tuhan. Etika berpakain yang baik dan sopan merupakan harta dan kemuliaan perempuan. Dalam kebaktian ada banyak cara berpakaian yang tidak sopan. Perempuan yang baik dan menjaga kehormatannya menjaga etika berpakaiannya. Dalam hal ini, penulis menggunakan metode kepustakaan dan ekegesis berdasarkan nas yang menjadi acuan penulis untuk mengungkapkan kebenaran tentang berpakaian.